The Influence Of Current Ratio (Cr), Debt To Equity Ratio (Der), Total Asset Turnover (Tato), And Net Profit Margin (Npm) On Return On Equity (Roe) In Lq-45 Companies Listed On The Indonesian Stock Exchange (Bei ) Year 2013-2018 - Medianto Basuki; Tina Rosa; Burhanudin (LPPM Universitas Respati Indonesia, 2024)
This study aims to analyze the effect of the Current Ratio, Debt to Equity Ratio (DER), Total Asset Turn Over (TATO) and Net Profit Margin (NPM) on LQ45 companies' Return on Equity (ROE) at the Indonesia Stock Exchange in 2013 - 2018. This research is an explanatory research that explains the causality relationship using secondary data with a population of 45 companies incorporated in the LQ45 index on the Indonesia Stock Exchange in 2018. Samples of 7 companies were selected using the purposive sample method in accordance with predetermined criteria including one of which is to have a report finance in 2013-2018. The analytical method used is panel data linear regression. The results showed that at the 95% confidence level of the four dependent variables studied, namely: Current Ratio, Debt to Equity Ratio (DER), Total Asset Turn Over (TATO) and Net Profit Margin (NPM) there are three variables that have a significant effect on Return on Equity (ROE), namely Debt to Equity Ratio (DER), Total Asset Turn Over (TATO) and and Net Profit Margin (NPM). Meanwhile, if tested simultaneously, the Current Ratio, Debt to Equity Ratio (DER), Total Asset Turn Over (TATO) and Net Profit Margin (NPM) have a significant effect on Return on Equity (ROE.) Keywords : Current Ratio, Debt to Equity Ratio (DER), Total Asset Turn Over (TATO) dan Net Profit Margin (NPM) dan Return on Equity (ROE)